A Designed, Highly Efficient Pyrrolysyl-tRNA Synthetase Mutant Binds o-Chlorophenylalanine Using Two Halogen Bonds. Issue 8 (30th April 2022) - Vatansever, Erol C.; Yang, Kai S.; Geng, Zhi Zachary; Qiao, Yuchen; Li, Pingwei; Xu, Shiqing; Liu, Wenshe Ray
Graphical abstract: Highlights: With two mutations at the active site, M. mazei pyrrolysyl-tRNA synthetase is engineered to efficiently mediate o -chlorophenylalanine at amber codon. The incorporation efficiency is much higher than that of N ε - Boc-lysine mediated by the wild-type enzyme. The X-ray crystallography analysis of the engineered enzyme bound with o -chlorophenylalanine shows that o -chlorophenylalanine involves two halogen bonds to bind at an inactive pocket of the enzyme. This is one of very few examples that a protein involves halogen bonds to bind its ligand. Abstract: As one of the most valuable tools for genetic code expansion, pyrrolysyl-tRNA synthetase (PylRS) is structurally related to phenylalanyl-tRNA synthetase (PheRS). By introducing mutations that mimic ligand interactions in PheRS into PylRS, we designed a PylRS mutant. This mutant, designated as oClFRS, recognizes a number of o -substituted phenylalanines for their genetic incorporation at amber codon. Its efficiency in catalyzing genetic incorporation of o -chlorophenylalanine ( o -ClF) is better than that for N ε - tert -butyloxycarbonyl-lysine catalyzed by PylRS. The crystal structure of oClFRS bound with o -ClF shows that o -ClF binds deeply into a hydrophobic but catalytically inactive pocket in the active site and involves two halogen bonds to achieve strong interactions. The shift of o -ClF to a catalytically active position in the oClFRS active site will be necessary for its activation. This is the first reported aminoacyl-tRNA synthetase that involves two halogen bonds for ligation recognition and might represent an alternative route to develop aminoacyl-tRNA synthetase mutants that are selective for noncanonical amino acids over native amino acids.